Mix it and fix it: functions of composite olfactory signals in ring-tailed lemurs. Issue 4 (April 2016) - Greene, Lydia K.; Grogan, Kathleen E.; Smyth, Kendra N.; Adams, Christine A.; Klager, Skylar A.; Drea, Christine M.
Abstract : Animals communicating via scent often deposit composite signals that incorporate odorants from multiple sources; however, the function of mixing chemical signals remains understudied. We tested both a 'multiple-messages' and a 'fixative' hypothesis of composite olfactory signalling, which, respectively, posit that mixing scents functions to increase information content or prolong signal longevity. Our subjects—adult, male ring-tailed lemurs ( Lemur catta )—have a complex scent-marking repertoire, involving volatile antebrachial (A) secretions, deposited pure or after being mixed with a squalene-rich paste exuded from brachial (B) glands. Using behavioural bioassays, we examined recipient responses to odorants collected from conspecific strangers. We concurrently presented pure A, pure B and mixed A + B secretions, in fresh or decayed conditions. Lemurs preferentially responded to mixed over pure secretions, their interest increasing and shifting over time, from sniffing and countermarking fresh mixtures, to licking and countermarking decayed mixtures. Substituting synthetic squalene (S)—a well-known fixative—for B secretions did not replicate prior results: B secretions, which contain additional chemicals that probably encode salient information, were preferred over pure S. Whereas support for the 'multiple-messages' hypothesis underscores the unique contribution from each of an animal's various secretions, support for the 'fixative' hypothesis highlights the synergistic benefits of composite signals.